miR-19b-3p/PKNOX1 Regulates Viral Myocarditis by Regulating Macrophage Polarization - Jiahui, Chen; Jiadai, Zheng; Nan, Zheng; Rui, Zhou; Lipin, Huang; Jian, He; Wenzong, Zhu; Riyuan, Zhang (Frontiers in Genetics, 2022)
Objective: The purpose of this study was to study the role and mechanism of miR-19b-3p in regulating myocardial inflammation and injury of viral myocarditis in viral myocarditis induced by Coxsackievirus B3 (CVB3). A CVB3 infection mouse model was established, the survival rate of mice was recorded after different treatments, cardiac function was detected, the degree of myocardial inflammatory infiltration and injury was detected by immunohistochemical and biochemical analyses, miR-19b-3p and PKNOX1 expression in cardiac tissue and cardiac infiltrating macrophages was detected using RT-PCR, and isolated mouse bone marrow-derived macrophages and the differentiation of macrophages after different transfections were detected. Finally, the binding of miR-19b-3p and PKNOX1 was verified by the dual luciferase reporter gene. The results showed that the expression of miR-19b-3p was significantly downregulated in the cardiac tissue and infiltrating macrophages of CVB3-infected mice, while the expression of PKNOX1 was upregulated. Upregulation of miR-19b-3p has protective effects against CVB3-induced myocardial injury in mice, such as weight gain, prolonged survival, increased left ventricular ejection fraction and left ventricular short axis shortening, reduced inflammation, creatine kinase isoenzyme (CK)-MB, and lactate dehydrogenase (LDH), and aspartate aminotransferase (AST) levels decreased, while interferon-γ and interleukin-6 (IL-6) increased, and the M2/M1 cell ratio was upregulated. In conclusion, miR-19b-3p can regulate macrophage polarization by targeting PKNOX1, and has a protective effect against CVB3-induced inflammation and myocardial injury.